Efficiency of farm yard manure to mitigate drastic saline water impacts on nutrients uptake by sorghum (Sorghum bicolor) - Murtaza, Ghulam; Sarwar, Ghulam; Manzoor, Muhammad Zeeshan; Zafar, Ayesha (Journal of Pure and Applied Agriculture, 2023)
The continuous use of saline water results in salt buildup in soil leading to reduced crop yield as well as soil resource deterioration. However, adding organic matter in either form may help in lowering salts in the rhizosphere. A trial was conducted to examine the efficacy of farm yard manure (FYM) in modifying the salinity and enhancing the uptake of nutrients by sorghum. In this experiment irrigation, water of 3 different types (canal water and saline water of electrical conductivity values 2 and 3 dS m -1 ) was applied and coupled with FYM @ 5 and 10 Mg ha-1 . The experiment was comprised of 9 treatments; T1= Canal Water, T2 = water of EC 2 dS m-1 , T3 = water of EC 3 dS m -1 , T4 = T1 + FYM @ 5 Mg ha-1 , T5 = T2 + FYM @ 5 Mg ha-1 , T6 = T3 + FYM @ 5 Mg ha-1 , T7 = T1 + FYM @ 10 Mg ha-1 , T8 = T2 + FYM @ 10 Mg ha-1 and T9 = T3 + FYM @ 10 Mg ha1 . The experiment was laid according to RCBD with four replications. Sorghum cultivar “Hegari” was grown as a test crop. Pre and post-harvest soil analysis was carried out for various soil characteristics. Results indicated that among all the treatments, T7 (T1 + FYM @ 10 Mg ha-1 ) performed best in enhancing N, P, K, Ca and Mg uptake while lowering the uptake of Na by sorghum. However, the treatment T3 (water of EC 3.0 dS m -1 ) lowered N, P, K, Ca and Mg uptake while enhancing sodium content in sorghum plants. © 2020 Department of Agricultural Sciences, AIOU